Proteomics for comprehensive characterization of extracellular vesicles in neurodegenerative disease - Vinaiphat, Arada (2022)
Extracellular vesicles (EVs) are small lipid bilayer particles ubiquitously released by almost every cell type. A specific and selective constituents of EVs loaded with variety of proteins, lipids, small noncoding RNAs, and long non-coding RNAs are reflective of cellular events, type, and physiologic/pathophysiologic status of the cell of origin. Moreover, these molecular contents carry information from the cell of origin to recipient cells, modulating intercellular communication. Recent studies demonstrated that EVs not only play a neuroprotective role by mediating the removal of toxic proteins, but also emerge as an important player in various neurodegenerative disease onset and progression through facilitating of misfolded proteins propagation. For this reason, neurodegenerative disease-associated differences in EV proteome relative to normal EVs can be used to fulfil diagnostic, prognostic, and therapeutic purposes. Nonetheless, characterizing EV proteome obtained from biological samples (brain tissue and body fluids, including urea, blood, saliva, and CSF) is a challenging task. Herein, we review the status of EV proteome profiling and the updated discovery of potential biomarkers for the diagnosis of neurodegenerative disease with an emphasis on the integration of high-throughput advanced mass spectrometry (MS) technologies for both qualitative and quantitative analysis of EVs in different clinical tissue/body fluid samples in past five years.